ANALISIS BISNIS RITEL DENGAN PENDEKATAN BLUE OCEAN STRATEGY DALAM MENCIPTAKAN INOVASI NILAI DI 212 MART PEKANBARU - Ismu Kusumanto; Della Arinda Fitri (Universitas Ahmad Dahlan Indonesia, 2019)
Minimarket 212 Mart is a sharia-based retail that provides goods for people who are only registered as Halal by MUI. The meeting of the number of minimarkets created a competition for the same market in Tampan District. 212 Mart is in the same battle area as other retailers such as Indomaret. So that more and more retails are destroying each other, killing each other and bleeding bloody termed the Red Ocean. The purpose of this study is to determine the position of the 212 Mart quadrant in retail competition anddesign a strategy that is applied by 212 Mart based on the Blue Ocean Strategy. Questionnaire data collection techniques for 100 respondents who are consumers 212 Mart Tampan District. Based on the research results 212 Mart is in quadrant III SWOT matrix which means it has a great opportunity but there are weaknesses in the company's internal. The 212 Mart strategy canvas shows the low value of competitors' curves, meaning the lack of offerings given to consumers. The results of the four-step framework, there are no eliminated factors, reducing factors that are notimportant in the competition, increasing factors that have a low value from Indomaret namely product variables, price, promotion, place, physical evidence, factors created include fresh corner, member card, giving coupons or sweepstakes, discount corners, non-cash payments, Where to provide hot drinks